Bending model for composite UHPFRC-RC elements including tension stiffening and crack width. (15th April 2020) - Zanuy, Carlos; Ulzurrun, Gonzalo S.D.
Highlights: A model for bending of UHPFRC-RC is proposed with mechanically sound compatibility condition. Stress transfer mechanism at the composite tension chord and crack widths are included. The model is contrasted with DIC-extracted crack width measurements of beam tests. Abstract: The application of a thin ultra-high performance fiber-reinforced concrete (UHPFRC) layer at the tensile side of reinforced concrete (RC) elements has lead to an efficient structural concept with promising capacities. Composite UHPFRC-RC elements have an increased bending capacity with respect to the RC member. In addition, the serviceability and durability are also improved as the composite element has higher stiffness and smaller crack widths. In order to widen the application of composite UHPFRC-RC elements, practitioners and designers need analytical and numerical tools with a sound mechanical background, if possible conceptually analogous to well-established models for conventional concrete structures. The paper starts with a discussion of the main drawbacks of existing models for UHPFRC-RC elements in bending. Secondly, new experimental basis is provided with own tests where the digital image correlation (DIC) technique is exploited to understand the crack pattern development and interfacial behaviour of UHPFRC-RC. Finally, the main goal of the paper is the proposal of a new model for UHPFRC-RC elements in bending which includes tension stiffening and the interaction at the steel-concrete and concrete-UHPFRC interfaces by means of a new composite tension chord model. The tension chord model is based on the stress transfer mechanisms between adjacent cracks, which include the explicit consideration of bond stresses between the constituent materials (i.e. steel and concrete, and UHPFRC and concrete). The compatibility condition between the UHPFRC and the RC layers is established in terms of the extension of each layer between adjacent cracks, as the classic compatibility of strains based on perfect bond assumption cannot be used upon macrocrack formation. Rather, the extension of the UHPFRC layer includes the contribution of cross-sections within the elastic, hardening or softening stages of the UHPFRC. The proposed model allows estimating the whole bending response, including calculation of crack widths and average curvatures between cracks.